2020
DOI: 10.15407/eip2020.04.007
|View full text |Cite
|
Sign up to set email alerts
|

Ukraine's pharmaceuticals: from dependence to endogenous development

Abstract: The article substantiates various theoretical and applied principles of developing high-tech pharmaceutical industries (HTPI). It is established that the key problem of developing countries in this area is the dependence on resources and markets of developed countries, while the involvement of advanced foreign technologies can be a catalyst for increasing the technological potential of host countries (subject to the availability of proper knowledge and human capital, changes in the institutional environment, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0
1

Year Published

2021
2021
2021
2021

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 11 publications
0
4
0
1
Order By: Relevance
“…The deterioration of the economy due to COVID-19 prompted the Cabinet of Ministers of Ukraine to adopt regulations to stimulate the economy, identifying among key activities the production of essential pharmaceutical products and preparations [2]. Among the short-term initiatives, it is among the following measures are indicated: "Financing research, development and innovation projects aimed at preventing the emergence and spread of COVID-19" with a planned allocation for 2020 of UAH 500 thousand 15 , or USD 17.58 thousand (at the NBU official exchange rate on 01.11.2020).…”
Section: Figure 5 Financial Assistance For Projects Addressing Pandem...mentioning
confidence: 99%
See 3 more Smart Citations
“…The deterioration of the economy due to COVID-19 prompted the Cabinet of Ministers of Ukraine to adopt regulations to stimulate the economy, identifying among key activities the production of essential pharmaceutical products and preparations [2]. Among the short-term initiatives, it is among the following measures are indicated: "Financing research, development and innovation projects aimed at preventing the emergence and spread of COVID-19" with a planned allocation for 2020 of UAH 500 thousand 15 , or USD 17.58 thousand (at the NBU official exchange rate on 01.11.2020).…”
Section: Figure 5 Financial Assistance For Projects Addressing Pandem...mentioning
confidence: 99%
“…The development of pharmacy in Ukraine, as noted in [2], has a number of obstacles. It is revealed that the small amount of the government request for training pharmacists at public expense and the low admission rates to training in the specialties of "pharmacy" and "industrial pharmacy" cause a shortage of specialists and personnel shortage in the sector.…”
Section: Figure 5 Financial Assistance For Projects Addressing Pandem...mentioning
confidence: 99%
See 2 more Smart Citations
“… здійснення досліджень і розробок (ДіР) як джерела технологічних інновацій;  нагромадження знань і навичок кваліфікованого персоналу як носія технологій;  активізація підприємницької діяльності як механізму трансформації ресурсів у нові процеси, товари та послуги. Проте ці процеси, за теорією залежності, мають перешкоди в країнах, що розвиваються: залежність від іноземних технологічних ресурсів і ринків, а також брак ендогенних інновацій [16]. Але в епоху глобалізації з'явилася нова форма залежності -розвинених країн від країн, що розвиваються, зокрема в поставках проміжних товарів для фармвиробництва та готових ЛЗ і МВ для системи охорони здоров'я.…”
unclassified